Examining the role of psychological need satisfaction in sleep: A Self-Determination Theory perspective. (April 2015) - Campbell, Rachel; Vansteenkiste, Maarten; Delesie, Liesbeth M.; Mariman, An N.; Soenens, Bart; Tobback, Els; Van der Kaap-Deeder, Jolene; Vogelaers, Dirk P.
Highlights: Low need satisfaction related to poor sleep quality and daytime dysfunction. Need satisfaction was positively associated with sleep quantity. Mindfulness and financial strain related to sleep quality via need satisfaction. Psychological need satisfaction may represent a critical explanatory mechanism. Abstract: Although ample research has shown the satisfaction of the basic psychological needs for autonomy, competence, and relatedness, as defined within Self-Determination Theory, to be related to well-being, the relation with sleep-related functioning has not yet been examined. Hence, the present study explored the association between basic psychological need satisfaction and subjective measures of sleep and daytime dysfunction, as well as the explanatory role of need satisfaction in the relation between mindfulness and financial strain and these outcomes, in an adult sample ( N  = 215, 61% female; Mean age = 31). The results indicated that low psychological need satisfaction related to poor sleep quality, lower sleep quantity, and more daytime dysfunction. Finally, mindfulness and financial strain related, respectively, negatively and positively to poor sleep quality and daytime dysfunction through need satisfaction, suggesting that need satisfaction represents a critical explanatory mechanism. The role of psychological need satisfaction in the adequate regulation and satisfaction of the physiological need for sleep is discussed.